New x-men by grant morrison, volume 2 ebook Imperial. - Morrison, Grant (New X-Men (2001), 2014)
Collects New X-Men (2001) #118-126. John Sublime and his U-Men launch an attack on the X-Men while a villain thought long gone makes their reappearance. Author: Grant Morrison. Illustrator: Frank Quitely, Igor Kordey, Ethan Van Scriver. © 2019 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com